2019
DOI: 10.1074/jbc.ra118.005550
|View full text |Cite
|
Sign up to set email alerts
|

A versatile mouse model of epitope-tagged histone H3.3 to study epigenome dynamics

Abstract: Edited by John M. Denu The authors declare that they have no conflicts of interest with the contents of this article. This article contains Tables S1-S3 and Figs. S1-S6. The raw sequence reads from RNA-seq experiments have been submitted in the NCBI Gene Expression Omnibus (http://www.ncbi.nlm.nih.gov/geo/) and are accessible through Gene Expression Omnibus series accession number GSE118926.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…We found that exogenously added H3.3 was preferentially incorporated into transcriptionally active genes, rather than inactive genes. This distribution pattern is consistent with many previous studies ( Bachu et al, 2019 ; Mito et al, 2005 ; Pchelintsev et al, 2013 ). The RhIP-ChIP-qPCR analysis also demonstrated the H3.3 enrichment at the transcriptionally active GAPDH, as compared to that at the inactive gene, LNC02199 ( Figure 1—figure supplement 1B and C ).…”
Section: Resultssupporting
confidence: 93%
“…We found that exogenously added H3.3 was preferentially incorporated into transcriptionally active genes, rather than inactive genes. This distribution pattern is consistent with many previous studies ( Bachu et al, 2019 ; Mito et al, 2005 ; Pchelintsev et al, 2013 ). The RhIP-ChIP-qPCR analysis also demonstrated the H3.3 enrichment at the transcriptionally active GAPDH, as compared to that at the inactive gene, LNC02199 ( Figure 1—figure supplement 1B and C ).…”
Section: Resultssupporting
confidence: 93%
“…Further, as we find here (fig. S3), H3.3 is enriched at inflammatory genes, though its function in this context is unknown 6,30 . To study the function of H3.3 in inflammatory gene induction we generated H3f3a/H3f3b double knockout (DKO) RAW264.7 (macrophage-like) mouse cell lines through CRISPR targeting of both H3f3a and H3f3b .…”
mentioning
confidence: 99%
“…MEFs were also isolated from these mice and immortalized as described previously (24). The expression levels of ISGs, Viperin , bone marrow stromal cell antigen-2 ( Bst-2 ), Isg15 , Isg54 , myxovirus resistance dynamin like GTPase 2 ( Mx2 ), guanylate binding protein 2 ( Gbp2 ), and Isg56 that are known to be highly increased in cells upon IFN stimulation (3638394041), were measured in WT and viperin KO BMDMs or MEFs (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%